Substance Abuse and Impaired Practice in Nursing - Yusrita Zolkefli (Iran University of Medical Sciences, 2024)
The healthcare community is becoming increasingly concerned about the potential compromise of clinical judgment among nurses due to substance abuse. In the context of the impaired practice of nurses using substance abuse, moral responsibility has emerged as one of the most significant ethical concerns.